2019
DOI: 10.3390/ijms20112709
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Protection of Biological Membranes during Lipid Peroxidation: Study of the Interactions between Flavonoid Loaded Mesoporous Silica Nanoparticles and Model Cell Membranes

Abstract: Flavonoids, polyphenols with anti-oxidative activity have high potential as novel therapeutics for neurodegenerative disease, but their applicability is rendered by their poor water solubility and chemical instability under physiological conditions. In this study, this is overcome by delivering flavonoids to model cell membranes (unsaturated DOPC) using prepared and characterized biodegradable mesoporous silica nanoparticles, MSNs. Quercetin, myricetin and myricitrin have been investigated in order to determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
(86 reference statements)
2
18
0
Order By: Relevance
“…ROS are shown to peroxidize lipids such as polyunsaturated fatty acids (PUFAs), which finally form malondialdehyde (MDA). The particular reaction of ROS with lipids is generally known as “lipid peroxidation.” In this study, we showed that the TOCP exposure led to a significant increase of malondialdehyde (MDA), accompanying with remarkable plunge of GSH levels and impaired enzymatic activity of SOD and GSH‐PX in the mouse ovarian granulosa cells. There was also a significant increase in intracellular ROS level in the TOCP‐treated cells.…”
Section: Discussionsupporting
confidence: 61%
“…ROS are shown to peroxidize lipids such as polyunsaturated fatty acids (PUFAs), which finally form malondialdehyde (MDA). The particular reaction of ROS with lipids is generally known as “lipid peroxidation.” In this study, we showed that the TOCP exposure led to a significant increase of malondialdehyde (MDA), accompanying with remarkable plunge of GSH levels and impaired enzymatic activity of SOD and GSH‐PX in the mouse ovarian granulosa cells. There was also a significant increase in intracellular ROS level in the TOCP‐treated cells.…”
Section: Discussionsupporting
confidence: 61%
“…The antioxidant activity of flavonoids is directly proportional to the number and position of hydroxyl groups in their structure [97], that assist in the dissipation of electrons generated after UV-overexposure [98]. Additionally, they also prevent lipid peroxidation [99] (by decomposing lipid peroxides and scavenging harmful free-radicals) and develop an effective metal chelation activity [100]. The free-radical scavenging [62,101,102] and lipid oxidation preventing activities [64] of Bryophyllum-derived extracts rich in flavonoids have already been reported.…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…It is an important component of the human’s daily diet and widely distributed in vegetables and fruits such as onions, tomatoes, berries, grapes, nuts, as well as in many flowers and leaves [ 2 , 3 ]. In addition, quercetin exhibits a wide range of biological and pharmacological activities, including antioxidant, anti-inflammatory, antibacterial, anti-anaemic, and anticarcinogenic activities [ 1 , 3 , 4 , 5 ]. Extensive studies have reported that quercetin can inhibit the proliferation of several types of cancers such as lung, prostate, breast cancer, and pancreatic tumour cells [ 1 ].…”
Section: Introductionmentioning
confidence: 99%